Roman Colchester - Hull, M.R (Reports of the Research Committee of the Society of Antiquaries of London, 1958)
This is a report of excavations at Colchester, in Essex, England, conducted by M. R. Hull. Included are descriptions of artefacts such as pottery, coins, buildings and metalwork, together with an account of the methodology used to unearth these.